2006
DOI: 10.1039/b516355b
|View full text |Cite
|
Sign up to set email alerts
|

A DFT study of the structures of pyruvic acid isomers and their decarboxylation

Abstract: Pyruvic acid and its isomers, including the enol tautomers and enantiomeric lactone structures, have been investigated at the B3LYP/6-311 + + G(3df,3pd) level, and it is found that a keto form with trans C(methyl)C(keto)C(acid)O(hydroxyl) and cis C(keto)C(acid)OH, and with one methyl hydrogen in a synperiplanar position with respect to the keto oxygen, is the most stable. This agrees with previous theoretical and experimental determinations. However, no minimum corresponding to protonated pyruvate could be loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
46
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 30 publications
(49 citation statements)
references
References 50 publications
3
46
0
Order By: Relevance
“…Also, keto–enol tautomerism and isomerization in pyruvic acid have been well studied experimentally and theoretically . Kakkar et al theoretically investigated the stability of isomers of pyruvic acid in the gas phase using the density functional theory. They found that a keto form with trans methylgroup‐C keto ‐C acid ‐O hydroxyl and cis C keto ‐C acid ‐O‐H, and one methyl hydrogen in a synperiplanar position with respect to the keto‐oxygen, is the most stable isomer.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Also, keto–enol tautomerism and isomerization in pyruvic acid have been well studied experimentally and theoretically . Kakkar et al theoretically investigated the stability of isomers of pyruvic acid in the gas phase using the density functional theory. They found that a keto form with trans methylgroup‐C keto ‐C acid ‐O hydroxyl and cis C keto ‐C acid ‐O‐H, and one methyl hydrogen in a synperiplanar position with respect to the keto‐oxygen, is the most stable isomer.…”
Section: Introductionmentioning
confidence: 99%
“…Keto–enol tautomerism of pyruvic acid is mainly studied experimentally . The theoretical studies are almost related to the stability of pyruvic acid tautomers and isomers in the gas phase and solution . The keto–enol tautomerism processes between the enol and keto forms of pyruvic acid have not been studied, theoretically.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Decarboxylation of pyruvic acid and its isomers, including the enol tautomers and enantiomeric lactone structures, has been investigated at the B3LYP/6-311++G(3df, 3pd) level. 18 It has been found that a keto form with trans C methyl C keto C acid O hydroxyl and cis C keto C acid OH, and with one methyl hydrogen in a synperiplanar position with respect to the keto oxygen, is the most stable.…”
Section: Acid Derivativesmentioning
confidence: 99%